2020
DOI: 10.1002/ange.202011137
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time Monitoring Reveals Dissolution/Redeposition Mechanism in Copper Nanocatalysts during the Initial Stages of the CO2 Reduction Reaction

Abstract: Size,m orphology,a nd surface sites of electrocatalysts have amajor impact on their performance.Understanding how, when, and why these parameters change under operating conditions is of importance for designing stable,a ctive,a nd selective catalysts.Herein, we study the reconstruction of aCubased nanocatalysts during the startup phase of the electrochemical CO 2 reduction reaction by combining results from electrochemical in situ transmission electron microscopyw ith operando X-ray absorption spectroscopy. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 58 publications
3
31
0
Order By: Relevance
“…[145][146][147][148][149][150][151][152] Furthermore, in situ TEM has been implemented to investigate materials involved in electrochemical processes, which is essential for understanding the operando structure-modified mechanisms of electrocatalysts. [153][154][155][156][157][158] For instance, Zhu et al used EC-TEM to gain deeper insight into the degradation mechanisms of Pt-Fe nanocatalysts. [153] They demonstrated that the coarsening processes of Pt-Fe electrocatalyst particles were not uniform, with the growth rate dependent on both the site and the applied potential.…”
Section: In Situ Temmentioning
confidence: 99%
See 2 more Smart Citations
“…[145][146][147][148][149][150][151][152] Furthermore, in situ TEM has been implemented to investigate materials involved in electrochemical processes, which is essential for understanding the operando structure-modified mechanisms of electrocatalysts. [153][154][155][156][157][158] For instance, Zhu et al used EC-TEM to gain deeper insight into the degradation mechanisms of Pt-Fe nanocatalysts. [153] They demonstrated that the coarsening processes of Pt-Fe electrocatalyst particles were not uniform, with the growth rate dependent on both the site and the applied potential.…”
Section: In Situ Temmentioning
confidence: 99%
“…Vavra et al used EC-TEM to study the reconstruction of Cu nanoparticle catalysts during the beginning phases of electrochemical CO 2 reduction. [155] As with similar EC-TEM studies, they used an electrochemical chip with a glassy carbon working electrode that provides a suitable support for the nanoparticle catalyst. This work indicated that Cu dissolution followed by redeposition, rather than coalescence, was the mechanism responsible for the observed size increase and morphological change of the electrocatalyst.…”
Section: In Situ Temmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of remaining latent variables is defined by the operator and here is typically set at 2. The rVAE's encoder had two convolutional layers with 128 filters ("kernels") of size (3,3) in each layer activated by leaky-ReLU function with a negative slope of 0.1. The rVAE's decoder consisted of two fully-connected ("dense") layers with 128 neurons in each layer activated by tanh().…”
mentioning
confidence: 99%
“…For instance, liquid phase and electrochemical STEM have enabled observation of battery devices operation, [1] morphogenesis of the electrodeposition and electroplating, [2] and structural evolution during electrocatalysis. [3] Environmental STEM has offered insights into the mechanisms of nanoparticle and nanowire growth. [4] Finally, elementary mechanisms of beam-induced reactions in layered dichalcogenides and graphene, [5][6][7][8][9][10][11][12][13][14] as well as certain bulk materials, [15][16][17] have been obtained at the atomic level.…”
mentioning
confidence: 99%